2020
DOI: 10.1021/acs.energyfuels.0c01582
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Profile Mapping over a Catalytic Unit of a Hydrogen Passive Autocatalytic Recombiner: An Experimental and Computational Fluid Dynamics Study

Abstract: Passive autocatalytic recombiners (PARs) are used for the removal of accidentally released hydrogen inside confined spaces. The high catalyst surface temperature is an important safety issue to be considered in the use of a PAR. The ability to predict the catalyst surface temperature could be very useful in preventing the self-ignition and explosion of hydrogen inside the PAR. This study seeks to investigate the changes in temperature profiles of the PAR catalytic section upon variation of the inlet hydrogen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The performance of the PAR was evaluated for inputs of hydrogen concentrations in a range 2-5 vol%. In addition, the experimental results were compared with CFD simulated results, and they were in good agreement [131]. Therefore, PARs will likely play a key role in underground mining and NPPs' accident mitigation in the future.…”
Section: Chc For Hydrogen Safety Purposesmentioning
confidence: 75%
See 2 more Smart Citations
“…The performance of the PAR was evaluated for inputs of hydrogen concentrations in a range 2-5 vol%. In addition, the experimental results were compared with CFD simulated results, and they were in good agreement [131]. Therefore, PARs will likely play a key role in underground mining and NPPs' accident mitigation in the future.…”
Section: Chc For Hydrogen Safety Purposesmentioning
confidence: 75%
“…A similar catalyst section was tested in a study by ; the catalyst manufacturer was not specified. The authors found a ∆T of 341.2 • C over a tubular ceramic Pt/Al 2 O 3 washcoat catalyst [131].…”
Section: Chc For Hydrogen Safety Purposesmentioning
confidence: 97%
See 1 more Smart Citation
“…The PARs are used to apply the CHC process to remove hydrogen from the catalytic surface. Several types of PARs were studied and tested. …”
Section: Applications Of Chcmentioning
confidence: 99%
“…A temperature gradient (ΔT) of only 23 °C was recorded over 70 mm of the catalyst surface at 3 vol % hydrogen. By comparison, Malakhov et al 48 recorded a ΔT of 341 °C over a tubular ceramic Pt/Al 2 O 3 washcoat catalyst for a 75 mL/min hydrogen flow. According to Appel et al, 49 to suppress high entry temperatures of the Pt/Al 2 O 3 /SiC catalyst, the initial catalyst section must be efficiently cooled.…”
Section: Introductionmentioning
confidence: 99%